DECAMETER PULSARS AND TRANSIENTS SURVEY OF THE NORTHERN SKY. STATUS, FIRST RESULTS, MULTIPARAMETRIC PIPELINE FOR CANDIDATE SELECTION - Zakharenko, V. V.; Kravtsov, I. P.; Vasylieva, I. Y.; Mykhailova, S. S.; Ulyanov, O. M.; Shevtsova, A. I.; Skoryk, A. O.; Zarka, P.; Konovalenko, O. O. (Одеські астрономічні публікації, 2016)
We present the results of processing first 20% of Northern sky pulsars and transients survey using UTR-2 radio telescope. Data processing is done by an automatic pipeline that detects and outputs a large number of transient candidates (usually dispersed bursts). We have developed a multivariate pipeline for visual inspection of these candidates. By adjustment of input parameters of the pipeline the observer can substantially increase signal-to-noise ratio of detected signals as well as discriminate them from residual low-intensity interference with high significance. About 450 transient signals have passed the examination by the multivariate pipeline. Their distributions on the Galactic latitude and dispersion measure have been derived. The shape of the distributions suggests that these signals might be associated with cosmic sources of radio emission.